The gender stratification of income inequality among lawyers - Hagan, John [Verfasser] (My University, 1990)
"Lawyers play unique roles in creating new structures of stratification in the larger economy and in stratifying their own profession. Gender stratification within this profession produces income differences many times those observed in the larger labor force. Our analysis focuses on the changing structural settings, sectoral movements, and levels of class power that form gender specific mobility ladders for individuals in the profession. Each of these factors plays an independent role in the determination of earnings, usually to the advantage of men over women. More than a quarter of the difference in earnings of men and women lawyers can conservatively be attributed to gender discrimination." (author's abstract) ((en)) Der Beitrag stützt sich auf eine 1985 in Kanada durchgeführte Befragung zu den geschlechtsspezifischen Einkommensunterschieden bei AnwältInnen. Untersucht werden der sich wandelnde strukturelle Hintergrund, sektorale Bewegungen und die verschiedenen Machtebenen in ihrem Einfluss auf geschlechtsspezifische Mobilitätsprozesse beim beruflichen Aufstieg. (IAB)
Geschlecht und Einkommensunterschiede bei Rechtsanwälten
Keywords: S 6.4 Dienstleistungsberufe; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; P 1.3 Frauen; Soziale Schichtung; Geschlechtsspezifische Faktoren; Rechtsanwalt; Berufsproblem; Einkommensunterschied; Diskriminierung; Frauen in Einzelberufen; Frauenarbeit; Quantitative Angaben